The Influence of Carbon/Glass/Epoxy Hybrid Interfacial Adhesion on the Mode II Delamination Fracture Toughness - Monticeli, F. M. [UNESP] (2022)
The incorporation of two different reinforcements in the same matrix introduces distinct physical, mechanical, and chemical characteristics into it, which need to be evaluated. In addition, the interfacial adhesion also plays a significant role in the mechanical delamination performance. This study aims to analyze the carbon/glass/ epoxy hybrid interfacial adhesion behavior through a DMA analysis and the mode II delamination toughness regarding the application possibilities of hybrid composites. Hybrid composites feature a strong interface adhesion and a high hindrance of the motion molecular chain, which is caused by the chemical adhesion of glass/carbon/epoxy through the organosilane promotors of glass fibers. The inhomogeneous load distribution, combined with the restricted molecular motion and synergetic combination of reinforcement stiffness, induces a change in crack propagation (a tortuous path) which is characteristic of a high interfacial adhesion. Hybrid interfaces also improve the mechanical behavior of laminates in shear, tending to increase the strain energy release ratio for mode II delamination, compared with that of non-hybrid laminates.